Testosterone use and shorter electrocardiographic QT interval duration in men living with and without HIV. Issue 5 (3rd December 2020) - Hiremath, PG; Bhondoekhan, F; Haberlen, SA; Ashikaga, H; Palella, FJ; D'Souza, G; Budoff, MJ; Kingsley, LA; Dobs, AS; Post, WS; Soliman, EZ; Brown, TT; et al.
Abstract : Objectives: Testosterone usage (T‐use) may alter risk factors for sudden cardiac death in men living with HIV (MLWH). Electrocardiographic QT interval prolongation, which could potentiate ventricular arrhythmias, has previously been associated with HIV infection and, separately, with low testosterone levels. We investigated whether T‐use shortens the QT interval duration in MLWH and HIV‐uninfected men. Methods: We utilized data from the Multicenter AIDS Cohort Study, a prospective, longitudinal study of HIV infection among men who have sex with men. Multivariable linear regression analyses were used to evaluate associations between T‐use and corrected QT interval (QTc) duration. Results: Testosterone usage was more common in MLWH compared with HIV‐uninfected men (19% vs . 9%). In a multivariable regression analysis, T‐use was associated with a 5.7 ms shorter QT interval [95% confidence interval (CI): −9.5 to −1.9; P  = 0.003). Furthermore, stronger associations were observed for prolonged duration of T‐use and recent timing of T‐use. Conclusions: This study is the first known analysis of T‐use and QTc interval in MLWH. Overall, our data demonstrate that recent T‐use is associated with a shorter QTc interval. Increased T‐use duration above a threshold of ≥ 50% of visits in the preceding 5 years was associated with a shorter QTc interval while lesser T‐use duration was not.